2009
DOI: 10.1002/jor.20904
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity walking mechanics of young individuals with asymptomatic varus knee alignment

Abstract: Varus knee alignment is associated with an increased risk for developing medial knee osteoarthritis (OA). Medial knee OA is commonly associated with altered walking mechanics in the frontal and sagittal planes, as well as altered ground reaction forces. It is unknown whether these mechanics are present in young, asymptomatic individuals with varus knees. We expected that varus-aligned individuals would generally present with frontal plane mechanics that were similar to those reported for individuals with media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…These biomechanical differences should not be attributed to walking speed, as speed did not differ across time for any of the experimental conditions ( Table 2). The present data are comparable to similar previously collected data, 12,[27][28][29][30] indicating that our data-collection and -analysis methods were appropriate.…”
Section: Discussionsupporting
confidence: 90%
“…These biomechanical differences should not be attributed to walking speed, as speed did not differ across time for any of the experimental conditions ( Table 2). The present data are comparable to similar previously collected data, 12,[27][28][29][30] indicating that our data-collection and -analysis methods were appropriate.…”
Section: Discussionsupporting
confidence: 90%
“…Knee adduction moments can be modified by orthoses (32)(33)(34), variable-stiffness shoes (35), leg braces (36), and reduced walking velocity (37). Knee malalignment may be associated with alterations in foot angle in early adult life (38). Because it is easier to alter foot angulation, we assume that this occurred secondary to constitutional knee malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because knee adduction moment does not influence thigh rotation (20) or hip adduction moment (38). Alternatively, Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that individuals can successfully alter their gait mechanics using real-time feedback 1618 19. As an example, White et al studied a group of individuals with a unilateral hip replacement and associated reduced loading on their involved side 16.…”
Section: Introductionmentioning
confidence: 99%
“…Indications of learning include the retention of new motor skills, as well as their transfer to another unpractised activity 20. Addressing the issue of retention, both Crowell et al (2009) and Barrios et al (2008) reported that gait changes induced using real-time biomechanical feedback were retained at a 1-month follow-up 18 19. However, neither of these studies examined the transfer of the new motor skills to other activities.…”
Section: Introductionmentioning
confidence: 99%